АPPLICATION OF IMMERSIVE TECHNOLOGIES IN PROFESSIONAL TRAINING AND RE-TRAINING OF MILITARY SPECIALISTS - Prokopenko, Алла (Journal of Information Technologies in Education (ITE), 2023)
The article presents the author's vision of the possibilities of using immersive technologies in the training and retraining of military specialists, formed during a systematic review of scientific sources, the study of modern educational technological trends, the analysis of successful practices in the use of such technologies in education, supported by own experience of working with students of a military education institution and the the author's research results author's study of the most relevant areas and areas of development of digital competences of military specialists. The study of educational issues takes into account the tasks defined by the Strategic Defense Bulletin of Ukraine, the orders of the Ministry of Defense of Ukraine, a number of laws of Ukraine regarding military security in Ukraine. Attention is drawn to the expediency of introducing immersive technologies into the military education system. As a result of the survey, a generalization of domestic and foreign experience in the formation of digital competence of military specialists is presented, as well as the attitude towards and needs for increasing the professional level of readiness to apply modern educational technological trends are investigated. A comparative analysis of the obtained results was carried out to determine the need of military specialists for additional knowledge and skills in the field of digital technologies, in particular mixed reality technologies. According to the author, the use of immersive technologies, that is, immersion in the digital world, can become the main tool in the formation of a modern ecosystem of military education, which should combine the intellectual, scientific, professional, educational, technological potential of the subjects of the educational environment, on the basis of openness, distribution and adaptability. and fundamentally change approaches to building the educational process in the military education system. Keywords: Immersive technologies, digital competence, digital tools, the Armed Forces of Ukraine, military education, ICT, educational ecosystem.